Bioactive Glass: Methods for Assessing Angiogenesis and Osteogenesis - Crush, Jos; Hussain, Ali; Seah, K. T. M.; Khan, Wasim S. (Frontiers in Cell and Developmental Biology, 2021)
Biomaterials are playing an increased role in the regeneration of damaged or absent bone tissue in the context of trauma, non-union, infection or congenital abnormality. Restoration of not only the physical scaffold that bone provides, but also of its homeostatic functions as a calcium store and hematopoietic organ are the gold standards of any regenerative procedure. Bioactive glasses are of interest as they can bond with the host bone and induce further both bone and blood vessel growth. The composition of the bioactive glasses can be manipulated to maximise both osteogenesis and angiogenesis, producing a 3D scaffolds that induce bone growth whilst also providing a structure that resists physiological stresses. As the primary endpoints of studies looking at bioactive glasses are very often the ability to form substantial and healthy tissues, this review will focus on the methods used to study and quantify osteogenesis and angiogenesis in bioactive glass experiments. These methods are manifold, and their accuracy is of great importance in identifying plausible future bioactive glasses for clinical use.